Neoadjuvant Chemotherapy Versus Debulking Surgery in Advanced Tubo-Ovarian Cancers: Pooled Analysis of Individual Patient Data From the EORTC 55971 and CHORUS Trials. Issue 3 (March 2019) - Vergote, Ignace; Coens, Corneel; Nankivell, Matthew; Kristensen, Gunnar B.; Parmar, Mahesh K. B.; Ehlen, Tom; Jayson, Gordon C.; Johnson, Nick; Swart, Ann Marie; Verheijen, René; McCluggage, W. Glenn; Perren, Tim; et al.
Abstract : (Abstracted from Lancet Oncol 2018;19:1680–1687) Most women with carcinoma of the ovary, fallopian tube, or peritoneum (tubo-ovarian cancer) present with advanced disease and have a very poor prognosis. An essential therapeutic strategy in these women has been primary debulking surgery (PDS), but no randomized controlled trials have demonstrated an improved prognosis of patients with this strategy.